PENGARUH KOMBINASI EKSTRAK TEMULAWAK, JAHE, KEDELAI DAN KULIT UDANG TERHADAP FUNGSI HATI DAN GINJAL DIBANDINGKAN DENGAN NATRIUM DIKLOFENAK PADA PENDERITA OSTEOARTRITIS - Nyoman Kertia; Nastiti Hemas M.; Dewa Ayu G. N. (Majalah Obat Tradisional, 2011)
Objectives To evaluate the effect of Curcuma xanthorrhyza Roxb extract, ginger, soybean and shrimp shell in combination compared to diclofenac sodium to liver and kidney function of patients with osteoarthritis. Methods twenty one subjects randomly allocated to different groups (Trial and control = diclofenac group). The trial group were treated by the combination of 50 mg temulawak extract, 100 mg ginger, 50 mg soybean and 100 mg shrimp shell three times daily while the control groupwere treated by 25 mg diclofenac sodium three times daily for a couple of week. Blood sample was obtained before and after two weeks therapy to determine the liver enzymes SGOT and SGPT and also serum ureum and creatinin in order to monitor the kidney function. The study was a prospective randomized open end blinded evaluation (PROBE). Result both trial and diclofenac group show significantly increase of SGOT levels (p<0.05) but the difference change among these groups are not significant (p=0.312). In the trial group there was decreasing of SGPT level (p=0.871) whereas there was an increase in level of SGPT in diclofenac group (p=1.000) although the difference between these two was not statistically significant (p=0.912). The change of serum ureum and creatinin level were not significantly different in trial group compared to diclofenac (p>0.05). In the trial group there was decreasing of serum ureum level although not significant (p=0.214). Both trial and diclofenac group showed no statistically significant increasing of creatinin serum levels (p>0.05). Conclusion there is no statistically difference effect between using the combination of temulawak extract, ginger, soybean and shrimp shell compared to diclofenac sodium toward liver and kidney function of osteoarthritis patients during this two weeks treatment.